The Future of Connectivist Learning with the Potential of Emerging Technologies and AI in Thailand: Trends, Applications, and Challenges in Shaping Education - Wongwatkit, Charoenchai; Thongsibsong, Nontawat; Chomngern, Titiya; Thavorn, Soraya (วารสารวิทยาการเรียนรู้และศึกษาศาสตร์, 2023)
This article explores the integration of connectivist learning, emerging technologies, and artificial intelligence (AI) in Thai education, with an emphasis on the potential for transformative impact. Connectivist learning, based on social connections and networked learning, benefits from the incorporation of AI, virtual reality, and collaborative tools, leading to personalized, immersive, and collaborative learning experiences. The article discusses trends, innovations, and global examples that can inform the Thai educational context, while addressing challenges such as infrastructure limitations, digital literacy, and socioeconomic disparities. Recommendations for fostering connectivist learning in Thailand include cross-sector collaboration between educational institutions, government agencies, and technology companies to enhance educational equity, access, and workforce preparedness. By bridging the digital divide and fostering lifelong learning, critical thinking, and creativity, connectivist learning can contribute to a more equitable and prosperous society in Thailand. The article concludes by reflecting on the potential long-term impact of connectivist learning with emerging technologies and AI and emphasizes the importance of ongoing dialogue, research, and collaboration.